THE MAIN STAGE OF GEOECONOMIC FRAGMENTATION (World of finance, 2026)
Вступ. Після глобальної фінансової кризи 2008–2010 рр. ризик геоекономічної фрагментації (ГЕФ) став основним викликом економічному розвитку, сповільнюючи та підважуючи глобальну торгівлю. Вивчення і розуміння можливих наслідків цього явища стали однією з провідних тем економічних досліджень останнього часу. Основним драйвером ГЕФ є поляризація поглядів ключових глобальних гравців на формат функціонування глобальної економіки. У випадку Сполучених Штатів це найяскравіше проявилося в першу, а особливо в другу каденцію президентства Дональда Трампа, коли односторонні дії у сфері глобальної торгівлі почали виходити на перший план під час вирішення внутрішньополітичних і міжнародних суперечок.Мета – систематизувати й узагальнити ключові наукові роботи з проблематики ГЕФ, виокремити провідні дослідження та подати їх у хронологічному порядку відповідно до розгортання процесу ГЕФ.Результати. Визначено відмінності між поняттями “деглобалізація” та “геоекономічна фрагментація”, окреслено роль політичних рішень у перебудові торговельних зав’язків, інвестицій і глобальних ланцюгів поставок. Запропоновано періодизацію ГЕФ на три ключові етапи: посткризовий період (2008–2016), період загострення політичної конфронтації і консолідації (2017–2025) та сучасна фаза глобальної поляризації інтересів (2025–…).Висновки. Обґрунтовано ймовірність подальшого поглиблення ГЕФ та необхідність більш широкого вивчення цього процесу задля розуміння наслідків для глобальної та вітчизняної економіки. Introduction. Following the global financial crisis of 2008-2010, the risk of geo-economic fragmentation (GEF) has become a major challenge to economic development, slowing down and undermining global trade. Studying and understanding the possible consequences of this phenomenon has become one of the leading topics of recent economic research. The main driver of GEF is the polarization of view among key global players on the global economy/ In the case of the United States, this was evident during Donald Trump`s first and especially second term as president, when unlateral actions in the field of global trade began to come to the fore in resolving domestic and international disputes.The purpose of the article is to systematize and summarize key scientific works on the topic of the GEF, to identify leading studies and present them in chronological order in accordance with the development of the GEF process.Results. The paper highlights the differences between the concepts of “deglobalization” and “geoeconomic fragmentation”, outlines the role of political decisions in the restructuring of trade ties, investments and global supply chains. It proposes a periodization of the GEF into three key stages: the post-crisis period (2008–2016), the period aggravation of political confrontation and consolidation (2017–2025) and the current phase of global polarization of interests (2025– …). It also provides an overview of key publications that have formed the current paradigm of GEF research.Conclusions. The study substantiates the likelihood of further deepening of GEF and highlights the need for broader research into this process to fully understand its implications for both the global and domestic economies.